Analisis Bibliometrik Kewirausahaan Sosial Di Indonesia: Pemetaan Struktur Intelektual dan Kolaborasi Penelitian - Lizza Suzanti; Disman Disman; B Lena Nuryanti (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Social entrepreneurship has become a strategic approach to addressing social and economic problems, particularly in developing countries such as Indonesia. Research on this topic continues to grow; however, the mapping of its intellectual structure and research collaboration remains limited. This study aims to analyze research trends in social entrepreneurship in Indonesia, identify publication patterns, conceptual structures, and collaboration networks among researchers. The method used is bibliometric analysis, with data collected from the Scopus database covering the period from 2020 to 2024. The analytical tools employed include RStudio, VOSviewer, and Excel. The findings indicate that the main themes emerging in social entrepreneurship research in Indonesia include social innovation, sustainability, community empowerment, and the role of technology in developing social enterprises. Furthermore, research collaboration networks remain fragmented, with several major groups dominating publications. The study concludes that social entrepreneurship research in Indonesia is expanding with increasingly diverse focuses; however, stronger collaboration among researchers is needed to enhance the research ecosystem and support more sustainable implementation of social entrepreneurship.